2000
DOI: 10.1063/1.372334
|View full text |Cite
|
Sign up to set email alerts
|

Nonprobe radio-frequency plasma diagnostics method based on the power balance in an asymmetric capacitively coupled discharge

Abstract: An analytical semiquantitative theoretical model founded on the self-bias voltage dependence on the absorbed radio-frequency (rf) power of a strongly asymmetric capacitively coupled rf discharge has been developed. The model is applicable under gas-discharge conditions typical of technological etching devices and suggests an experimental method for determining basic plasma parameters, more specifically the ion flux onto the powered electrode, without using any additional probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The observed changes can be attributed to redistribution of rf power between the two main plasma regions in a capacitively coupled rf-driven discharge: the bulk plasma and the sheath. Studies of the power balance in an asymmetric rf discharge 23,24 have shown that the distribution depends criti-cally on the gases used, more specifically, on the losses of electron energy during lifetime of electrons in the bulk plasma. Two groups of gases may be distinguished.…”
Section: O 2 õN 2 õSf 6 Plasmasmentioning
confidence: 99%
“…The observed changes can be attributed to redistribution of rf power between the two main plasma regions in a capacitively coupled rf-driven discharge: the bulk plasma and the sheath. Studies of the power balance in an asymmetric rf discharge 23,24 have shown that the distribution depends criti-cally on the gases used, more specifically, on the losses of electron energy during lifetime of electrons in the bulk plasma. Two groups of gases may be distinguished.…”
Section: O 2 õN 2 õSf 6 Plasmasmentioning
confidence: 99%
“…Nevertheless, several attempts have been made to model this kind of plasmas (most work has been done for less electronegative plasmas), at least in a limited parameter range [1]. Recently, a simple power balance model has been proposed by Mateev and Zhelyazkov [3], [4] and applied by Moshkalyov and coworkers in order to predict etching trends in different low and medium pressure (≤ 50 mTorr) plasmas [5]. However, the formalism of the model does not take into account the effect of negative ions, and it is less justified when the ion free fall model of the sheath can not be applied.…”
Section: Introductionmentioning
confidence: 99%
“…The second boundary condition states that the ions enter the collisionless sheath at Bohm's speed v B [4]. The power P which the source of high-frequency voltage introduces into the plasma can be split into two parts [1]:…”
Section: Analytical Description Of a Space-charge Sheathmentioning
confidence: 99%
“…Following the method described in [1], from at least three experimental points of the U 0 (P ) dependence we determine those coe±cients B, C and D which best¯t the function…”
Section: Analytical Description Of a Space-charge Sheathmentioning
confidence: 99%
See 1 more Smart Citation